Agreement between parental reports and accelerometer measures of sleep duration in primary school children - Ana Duarte; Juliana Martins; Rafaela Rosário (Scientific Reports)
Abstract Sleep plays a critical role in children’s health and development, with sleep duration being one of the most commonly analyzed measures by researchers. Accurate assessment of sleep duration in school-aged children is crucial for understanding its impact on cognitive development, behavior, and overall health. However, discrepancies between parent-reported sleep duration and objective measurements, such as accelerometry, pose challenges in assessing sleep patterns in children. This study examines the agreement between accelerometer-measured and parent-reported sleep duration in school-aged children from socially vulnerable contexts. A total of 735 children from primary schools wore accelerometers for seven consecutive days, while parents reported their children’s sleep duration. The results revealed significant discrepancies, with parents generally overestimating sleep duration and demonstrating poor predictive accuracy. These findings underscore the need for more reliable methods in assessing sleep duration in children from socially vulnerable backgrounds. By highlighting the discrepancy between accelerometer data and parent reports, the study emphasizes the importance of objective measurements in sleep research. The study’s implications are particularly relevant for public health initiatives aimed at promoting healthy sleep habits among children in socioeconomically disadvantaged communities.